A Novel Hypomorphic PDX1 Mutation Responsible for Permanent Neonatal Diabetes With Subclinical Exocrine Deficiency - Nicolino, Marc (American Diabetes Association, 2010)
OBJECTIVE: Genes responsible for monogenic forms of diabetes have proven very valuable for understanding key mechanisms involved in β-cell development and function. Genetic study of selected families is a powerful strategy to identify such genes. We studied a consanguineous family with two first cousins affected by neonatal diabetes; their four parents had a common ancestor, suggestive of a fully penetrant recessive mutation. RESEARCH DESIGN AND METHODS: We performed genetic studies of the family, detailed clinical and biochemical investigations of the patients and the four parents, and biochemical and functional studies of the new mutation. RESULTS: We found a novel mutation in the pancreatic and duodenal homeobox 1 gene (PDX1, IPF1) in the two patients, which segregated with diabetes in the homozygous state. The mutation resulted in an E178G substitution in the PDX1 homeodomain. In contrast to other reported PDX1 mutations leading to neonatal diabetes and pancreas agenesis, homozygosity for the E178G mutation was not associated with clinical signs of exocrine pancreas insufficiency. Further, the four heterozygous parents were not diabetic and displayed normal glucose tolerance. Biochemical studies, however, revealed subclinical exocrine pancreas insufficiency in the patients and slightly reduced insulin secretion in the heterozygous parents. The E178G mutation resulted in reduced Pdx1 transactivation despite normal nuclear localization, expression level, and chromatin occupancy. CONCLUSIONS: This study broadens the clinical spectrum of PDX1 mutations and justifies screening of this gene in neonatal diabetic patients even in the absence of exocrine pancreas manifestations.